2010
DOI: 10.1103/physrevlett.105.024101
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Control of the Quantum Chaotic Dynamics of Hydrogen Analogs in an Anisotropic Crystal Field

Abstract: We report magnetic field control of the quantum chaotic dynamics of hydrogen analogues in an anisotropic solid state environment. The chaoticity of the system dynamics was quantified by means of energy level statistics. We analyzed the magnetic field dependence of the statistical distribution of the impurity energy levels and found a smooth transition between the Poisson limit and the Wigner limit, i.e. transition between regular Poisson and fully chaotic Wigner dynamics. Effect of the crystal field anisotropy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Identification of the observed spectral features is further hindered at these fields because the calculation of theoretical spectra where the magnetic cyclotron energy (:eB/m e ) is comparable to the coulombic binding energy (the Rydberg R ¼ m e e 4 /2k 2 : 2 , where k ¼ 4pe 0 ) is non-trivial, especially for atomic species other than hydrogen, such as helium [10][11][12] . The difficulty is that in the regime of interest (BBB 0 ¼ m e 2 e 3 /2k 2 : 3 ) the Zeeman effect becomes quadratic [13][14][15] , the spherical symmetry of the Coulomb potential competes with the cylindrical symmetry of the magnetic field, and the Schrodinger equation is non-integrable, so producing quantum chaos 16,17 . The theory for the very complex Zeeman structure in atoms has been compared with laboratory absorption spectra in magnetic fields up to 8 T (refs [13][14][15].…”
mentioning
confidence: 99%
“…Identification of the observed spectral features is further hindered at these fields because the calculation of theoretical spectra where the magnetic cyclotron energy (:eB/m e ) is comparable to the coulombic binding energy (the Rydberg R ¼ m e e 4 /2k 2 : 2 , where k ¼ 4pe 0 ) is non-trivial, especially for atomic species other than hydrogen, such as helium [10][11][12] . The difficulty is that in the regime of interest (BBB 0 ¼ m e 2 e 3 /2k 2 : 3 ) the Zeeman effect becomes quadratic [13][14][15] , the spherical symmetry of the Coulomb potential competes with the cylindrical symmetry of the magnetic field, and the Schrodinger equation is non-integrable, so producing quantum chaos 16,17 . The theory for the very complex Zeeman structure in atoms has been compared with laboratory absorption spectra in magnetic fields up to 8 T (refs [13][14][15].…”
mentioning
confidence: 99%
“…We have also shown that the quantum scar in AKP is robust and survives under the successive avoidance of level crossings during large variations in anisotropy [13]. Note that AKP can be realized by a semiconductor with donor impurity, and experimental manufacturing toward this goal has been reported [14,15].…”
Section: Introductionmentioning
confidence: 69%
“…X 0 changes rapidly after g th . 15 Our preliminary result, from numerical calculation of z ( ) X , 0 F P , 0…”
Section: The Two-dimensional Akp Po Searchmentioning
confidence: 99%
“…This observation implies that all antiunitary symmetries are broken in the system. However, for most of the physical systems still there is at least one antiunitary symmetry left [34][35][36][37][38][39][40][41][42][43]. This also holds for atoms in constant external fields [44][45][46].…”
Section: Introductionmentioning
confidence: 99%